Informational Needs of Postmastectomy Patients - Duygu Soydaş Yeşilyurt; Ümmü Yıldız Fındık (European Journal of Breast Health, 2016)

(untitled)
Objective: The aim of this study was to determine informational needs of postmastectomy patients.Materials and Methods: This descriptive study was conducted in the general surgery clinics of a university health center for medical research and practice with 72 voluntary patients. For data collection, a patient identification form was used, which was prepared by the researchers in accordance with the literature.Results: The mean age of the patients was 52.66±13.39 years, 87% were married, 58% had primary school education, 76% had moderate economic status, and 53% had undergone simple mastectomy. It was determined that 83% of the patients wanted to be informed about hospital and home care interventions, 82% about symptoms and prevention of post-surgical problems, 76% regarding breast cancer and treatment options, and in the range of 54-68%, patients wanted information on the effects of surgery on the body, shoulder and arm exercises, breast self-examination, the effects of breast cancer on family and work life, lymphedema and prevention interventions.Conclusion: We recommend that patients with mastectomy should be informed about topics including care interventions, breast cancer and treatment options, effects of surgery, and reducing these effects.